ERN GENTURIS tumour surveillance guidelines for individuals with neurofibromatosis type 1. (February 2023) - Carton, Charlotte; Evans, D. Gareth; Blanco, Ignacio; Friedrich, Reinhard E.; Ferner, Rosalie E.; Farschtschi, Said; Salvador, Hector; Azizi, Amedeo A.; Mautner, Victor; Röhl, Claas; Peltonen, Sirkku; Stivaros, Stavros; et al.
Summary: Background: Neurofibromatosis type 1 (NF1) is a multisystem genetic disorder, predisposing development of benign and malignant tumours. Given the oncogenic potential, long-term surveillance is important in patients with NF1. Proposals for NF1 care and its specific manifestations have been developed, but lack integration within routine care. This guideline aims to assimilate available information on NF1 associated tumours (based on evidence and/or expert opinion) to assist healthcare professionals in undertaking tumour surveillance of NF1 individuals. Methods: By comprehensive literature review, performed March 18th 2020, guidelines were developed by a NF1 expert group and patient representatives, conversant with clinical care of the wide NF1 disease spectrum. We used a modified Delphi procedure to overcome issues of variability in recommendations for specific (national) health care settings, and to deal with recommendations based on indirect (scarce) evidence. Findings: We defined proposals for personalised and targeted tumour management in NF1, ensuring appropriate care for those in need, whilst reducing unnecessary intervention. We also incorporated the tumour-related psychosocial and quality of life impact of NF1. Interpretation: The guideline reflects the current care for NF1 in Europe. They are not meant to be prescriptive and may be adjusted to local available resources at the treating centre, both within and outside EU countries. Funding: This guideline has been supported by the European Reference Network on Genetic Tumour Risk Syndromes (ERN GENTURIS). ERN GENTURIS is funded by the European Union . DGE is supported by the Manchester NIHR Biomedical Research Centre (IS-BRC-1215-20007 ).